A Big Challenge in a Tiny Heart: Right Ventricular Outflow Tract (RVOT) Stenting in a Premature Infant with Pentalogy of Fallot - Adnan Rhafif; Radityo Prakoso; Aditya Agita Sembiring (The Indonesian Heart Association, 2026)
Background: Pentalogy of Fallot (POF) is a cyanotic congenital heart defect characterized by five anatomical abnormalities: Ventricular Septal Defect (VSD), pulmonary stenosis, Right Ventricular Hypertrophy (RVH), an overriding aorta, and an Atrial Septal Defect (ASD). The presence of the additional ASD alongside the classic features of Tetralogy of Fallot (TOF) can further exacerbate right-to-left shunting and worsen systemic desaturation. Management of POF in premature infants is particularly challenging due to low birth weight, underdeveloped pulmonary vasculature, and increased surgical risks. In high-risk neonates, traditional surgical options such as the modified Blalock–Taussig shunt may not be feasible. Right Ventricular Outflow Tract (RVOT) stenting has emerged as a minimally invasive palliative alternative to improve oxygenation and promote pulmonary artery growth, serving as a bridge to definitive surgical repair. This case highlights the technical considerations of RVOT stenting in high-risk neonates, emphasizing its role as a bridge to definitive surgical repair. Case Illustration: An 11-day-old premature infant presented with progressive central cyanosis, desaturation episodes (<70%), and shortness of breath. Physical examination revealed respiratory distress, central cyanosis, and an ejection systolic murmur. Imaging showed a boot-shaped heart and oligemia, while echocardiography confirmed POF with severe RVOT obstruction, hypoplastic pulmonary arteries, and reduced Right Ventricular (RV) function. The patient was initially managed for a hypoxic spell but later developed periodic apnea and cardiac arrest, prompting additional diagnosis of apnea of prematurity and admission to the Intensive Care Unit (ICU) for further management. Despite treatment, worsening respiratory effort necessitated intubation. After clinical stabilization and extubation, persistent hypoxia led to RVOT stenting at 32 days of age. After initial difficulty, balloon pre-dilation allowed successful stent deployment, resulting in improved oxygen saturation. Conclusion: This case demonstrates the feasibility and effectiveness of RVOT stenting as a palliative strategy in a premature infant with POF. The intervention led to immediate improvement in oxygenation and allowed time for clinical stabilization and potential pulmonary artery growth. This highlights that, in selected high-risk neonates where conventional surgical options may be unsuitable, catheter-based palliation can serve as a critical bridge to definitive surgical repair.